Modern Methods of Furniture Design in the Interior of a Building of a Preschool Educational Organization (Journal of Architectural Design, 2022)
This article is aimed at studying modern methods of furniture design in the interior of the premises of a preschool educational organization (kindergartens) and developing proposals for their application in practice.